Manx crosses a handbook of stone sculpture 500-1040 in the Isle of Man - Wilson, David M. (David Mackenzie), 1931- (Archaeopress archaeology., 2018)
This is the first general survey of the carved stone crosses of the Isle of Man (late 5th to mid-11th century) for more than a century, providing a new view of the political and religious connections of the Isle of Man in a period of great turmoil in the Irish Sea region. The book also includes an up-to-date annotated inventory of the monuments.